The moderns : midcentury American graphic design - Heller, Steven; D'onofrio, Greg (Abrams, 2017)
In The Moderns, we meet the men and women who invented and shaped Midcentury Modern graphic design in America. The book is made up of generously illustrated profiles, many based on interviews, of more than 60 designers whose magazine, book, and record covers; advertisements and package designs; posters; and other projects created the visual aesthetics of postwar modernity. Some were émigrés from Europe; others were homegrown-all were intoxicated by elemental typography, primary colors, photography, and geometric or biomorphic forms. Some are well-known, others are honored in this volume for the first time, and together they comprised a movement that changed our design world.